A high-strength antistatic polyetheretherketone (PEEK) pipe and preparation method thereof
By using a combination technology of ultrasonic dispersed carbon nanotubes and crystalline polyaryletherketone nucleating agents in PEEK pipes, the problem of inseparable processability and high strength is solved, and high-strength, low-energy consumption, environmentally friendly anti-static electricity is achieved Polyether etherketone pipe preparation significantly improves mechanical properties and dimensional stability.
Patent Information
- Application Number
- CN202211499970.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-28
AI Technical Summary
In the prior art, when preparing high-strength anti-static polyether ether ketone (PEEK) pipes, the processability and high strength cannot be achieved, the anti-static filler is prone to agglomeration, the production process is poor safety and environmental protection, the internal stress is large and the dimensional stability is poor. Moreover, common modifiers cannot function stably at high temperatures, resulting in reduced mechanical properties and long production cycles.
Ultrasonic dispersion technology is used to uniformly distribute carbon nanotubes as antistatic fillers on the surface of PEEK ultrafine powder, and the filler is fixed using crystalline polyaryletherketone nucleating agent, and high-strength resistance is prepared by high-speed stirring and mixing and multi-stage vacuum heat-scaling process. Electrostatic polyether etherketone pipes significantly improve fluidity and crystallinity, eliminate internal stress, and improve dimensional stability and environmental protection.
It significantly improves the fluidity and mechanical properties of the pipe, enhances the antistatic and strength, shortens the preparation cycle, improves production safety and environmental protection, and eliminates the internal stress caused by thermal expansion and contraction, ensuring dimensional stability sex.
Smart Images

Figure CN116285213B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic pipe preparation, and in particular relates to a high-strength antistatic polyetheretherketone (PEEK) pipe and a preparation method thereof. Background Art
[0002] Polyetheretherketone (PEEK) is widely used in various fields due to its excellent heat resistance, solvent resistance and mechanical properties, especially in oil pipelines where the above advantages are fully utilized. However, organic polymer materials have poor electrical conductivity and are prone to accumulate static charges, which brings great dangers to their use. Therefore, it is urgent to develop an antistatic pipe with high strength and high dimensional stability. The existing technologies have the following problems:
[0003] a. Processability and high strength cannot be achieved at the same time. PEEK has a high melt viscosity, and its fluidity is worse after adding antistatic fillers, which makes it impossible to prepare pipes by extrusion. The common method to improve processability is to reduce the molecular weight of PEEK to obtain higher fluidity, which inevitably reduces the strength of the pipe;
[0004] b. Agglomeration of antistatic fillers. Commonly used antistatic fillers have small particle sizes, even nanometer-sized. The large surface energy of nanofillers will cause them to agglomerate in every step of pipe preparation;
[0005] c. Good antistatic properties and high strength cannot be achieved at the same time. In order to obtain good antistatic properties, a large amount of antistatic fillers must be used, which will seriously hinder the crystallization behavior of crystalline polymers, thereby causing a decrease in the mechanical properties of the pipe;
[0006] d. The production process is not safe and environmentally friendly. Antistatic fillers, especially nano antistatic fillers, are light and easy to float in the air, which not only pollutes the environment but also easily explodes and causes fires;
[0007] e. Common modifiers cannot bring into play the advantages of PEEK's high temperature resistance, solvent resistance and high strength. The processing temperature of polyetheretherketone is higher than 360°C, and common modifiers are difficult to function stably at this temperature; common modifiers are all soluble, which will lead to a decrease in the solvent resistance of PEEK pipes; common modifiers lack strong interaction with PEEK, which will cause stress concentration and thus reduce the mechanical strength of the pipe.
[0008] f. Large internal stress, poor dimensional stability and complicated process for eliminating internal stress. The crystallinity of PEEK causes internal stress caused by thermal expansion and contraction, as well as internal stress caused by crystallization shrinkage. Existing technologies can only eliminate the internal stress caused by thermal expansion and contraction, and require additional heat treatment processes, which not only leads to poor dimensional stability of the pipe, but also leads to long production cycles and energy waste.
[0009] Therefore, developing a high-strength antistatic polyetheretherketone (PEEK) material that has the advantages of processability, high temperature resistance, solvent resistance, dimensional stability, low energy consumption, environmental protection, short production cycle and safe preparation process is one of the research directions of technicians in this field. Summary of the invention
[0010] In order to solve the above technical problems, the present invention provides a high-strength antistatic polyetheretherketone (PEEK) pipe, and its preparation method comprises the following steps:
[0011] (1) dissolving a soluble precursor of a crystalline polyaryletherketone-based nucleating agent in an organic solvent to obtain a precursor solution with a mass fraction of 0.5-5.0wt%; then adding an antistatic filler under ultrasonic dispersion conditions, wherein the mass fraction of the antistatic filler in the precursor solution is 0.1-2.0wt%, and after ultrasonic dispersion for 10-60min, adding 100-300 mesh PEEK ultrafine powder with a mass fraction of 0.5-5.0wt%; and after ultrasonic dispersion for 10-60min, adding a protonic acid aqueous solution with a pH of 1-5, wherein the protonic acid aqueous solution The volume ratio of the solution to the organic solvent is 20-60%:1; after refluxing for 5-15 hours, the mixture is filtered, and then washed with an acid having a pH value of 1-5, washed with water, and washed with ethanol to obtain an antistatic masterbatch; the antistatic filler is evenly distributed in a single layer on the surface of the PEEK ultrafine powder; the crystalline polyaryletherketone-based nucleating agent is evenly attached to the surface of the PEEK ultrafine powder; the crystalline polyaryletherketone-based nucleating agent bonds the antistatic filler to the surface of the PEEK ultrafine powder; the antistatic filler is a carbon nanotube, and the melt index of the PEEK ultrafine powder is 80-144g / 10min;
[0012] (2) According to the mass ratio of 94.8-60:5-20:0.2-30, PEEK powder with a melt index of 5-50g / 10min and a mesh size of 100-1000, a polyaryletherketone-based plasticizer and the antistatic masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a rate of 10000-20000r / min for 10-30min, and then extruded and granulated to obtain a high-strength antistatic polyetheretherketone pipe raw material; among the raw materials: except for the antistatic filler, the remaining components are polyaryletherketone, the antistatic filler content is 0.1-10 parts, the crystalline polyaryletherketone-based nucleating agent content is 0.1-10 parts, the polyaryletherketone-based plasticizer content is 5-20 parts, and the PEEK content is 60-94.8 parts;
[0013] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is melted, extruded, vacuum sized, and then cooled, pulled, cut or curled to obtain a high-strength antistatic polyetheretherketone pipe; the vacuum sizing is as follows: the vacuum degree is 0.1-0.8MPa, three 6-10 m high-temperature sizing boxes are used to heat in three stages in sequence, the first stage cooling sizing temperature is 300-320°C, the second stage crystallization sizing temperature is 250-280°C, and the third stage annealing sizing temperature is 180-200°C; the pulling rate is 500-1000mm / min.
[0014] Further, the soluble precursor of the crystalline polyaryletherketone-based nucleating agent used in the above step (1) is ketimine-type polyetheretherketoneketone, hemiketal-type polyetheretherketoneketone, ketimine-type all-biphenyl-type polyetheretherketone, hemiketal-type all-biphenyl-type polyetheretherketone, ketimine-type all-biphenyl-type polyetheretherketoneketone, hemiketal-type all-biphenyl-type polyetheretherketoneketone, ketimine-type all-biphenyl-type polyetheretherketonebiphenylketone or hemiketal-type all-biphenyl-type polyetheretherketonebiphenylketone, and their structures are shown in the following structural formulas 1-8 in sequence;
[0015] Furthermore, the organic solvent used in step (1) is tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, 1,2-dichloroethane, chloroform or N-methylpyrrolidone;
[0016] Furthermore, the protonic acid used in step (1) is hydrochloric acid, sulfuric acid, methanesulfonic acid, benzenesulfonic acid, trifluoroacetic acid or trifluorobenzenesulfonic acid;
[0017] Furthermore, the carbon nanotubes described in step (1) are acidified carbon nanotubes.
[0018] Furthermore, the polyaryletherketone-based plasticizer used in step (2) is PEEK or hyperbranched polyaryletherketone or polyaryletherketone liquid crystal having a melt index of 100-150 g / 10 min, and the structure of the hyperbranched polyaryletherketone or polyaryletherketone liquid crystal is as shown in the following structural formula 9-10;
[0019] Furthermore, the extrusion in step (2) is performed by using a twin-screw extruder, wherein the speed is 220-280 r / min; the temperature of the feeding section is 250-300° C.; the temperature of the compression section and the side feeding section is 370-380° C.; the temperature of the homogenization section is 380-390° C.; and the temperature of the extrusion die is 365-385° C.;
[0020] Furthermore, the extrusion in step (3) is as follows: a single screw extruder is used, wherein the rotation speed is 40-60r / min; the temperature of the feeding section is 280-320°C; the temperature of the compression section is 370-380°C; the temperature of the homogenization section is 380-390°C; the temperature of the die head is 350-370°C; and the pulling rate is 10-500mm / min.
[0021]
[0022]
[0023]
[0024]
[0025] Features and benefits
[0026] The present invention obtains the following advantages through the synergistic effect of raw materials, proportions and reaction processes:
[0027] 1. Good compatibility with PEEK, good thermal stability and good solvent resistance; significantly increase the amount of antistatic filler added in the pipe (up to 20wt% by mass); significantly improve the fluidity of high molecular weight PEEK after adding antistatic filler (according to prior art reports: PEEK with a melt index of 10g / 10min loses fluidity after adding 10wt% of antistatic filler by mass and cannot be processed and formed. However, after adding 20wt% of polyaryletherketone-based plasticizer, the high-strength antistatic polyetheretherketone pipe raw material achieves a melt index of 12g / 10min and can be extruded into a pipe); significantly shorten the pipe preparation cycle, and the traction rate can reach 500mm / min;
[0028] 2. Coated on the surface of the antistatic filler to prevent it from agglomerating; fix the antistatic filler on the surface of the PEEK powder in the masterbatch stage to prevent dust and pollution, thereby improving production safety; significantly improve the crystallinity of the pipe (the crystallinity of the pipe without adding crystalline polyaryletherketone-based nucleating agent is 20-23%, and the crystallinity of the pipe with 10wt% crystalline polyaryletherketone-based nucleating agent is 28-35%), strength (the bursting pressure of the pipe without adding crystalline polyaryletherketone-based nucleating agent is 2.5MPa, and the bursting pressure of the pipe with 10wt% crystalline polyaryletherketone-based nucleating agent is 6.0MPa, an increase of 140% year-on-year) and pipe morphology (the pipe without adding crystalline polyaryletherketone-based nucleating agent is shown in the attached figure). Figure 1 The surface of the pipe is extremely rough and full of defects; the pipe with the addition of crystalline polyaryletherketone-based nucleating agent is shown in the attached Figure 2 The surface of the pipe is bright and almost defect-free; the comparison photos of the pipes with and without the addition of crystalline polyaryletherketone-based nucleating agent are attached. Figure 3);
[0029] 3. At the same time, the internal stress caused by thermal expansion and contraction and crystallization shrinkage is eliminated, and the good dimensional accuracy and dimensional stability of the pipe are guaranteed without the need for subsequent heat treatment processes.
[0030] 4. The present invention realizes low energy consumption, environmental protection, rapid preparation of antistatic PEEK pipes with good processability, high temperature resistance, solvent resistance and high dimensional stability, and the related advantages are as follows:
[0031] a. The method of compounding high molecular weight (low melt index) PEEK, plasticizer and antistatic filler solves the problem that processability and high strength cannot be achieved at the same time;
[0032] b. The crystallization behavior of PEEK is adjusted by compounding nucleating agent and antistatic filler, which solves the problem that good antistatic property and high strength cannot be achieved at the same time;
[0033] c. Use polyaryletherketone-based polymers with special structures as plasticizers and nucleating agents, which not only have the advantages of heat resistance and solvent resistance, but also have good compatibility with PEEK;
[0034] d. Developed a masterbatch consisting of antistatic filler, nucleating agent and PEEK, which not only solves the problem of easy agglomeration of antistatic filler, but also reduces its floating ability in the air, improving environmental protection and safety;
[0035] e. The one-step multi-stage vacuum heat sizing process replaces the traditional three-step process of "sizing-cooling-heat treatment", which improves the dimensional stability of the pipe, reduces energy consumption, and saves production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a photo of the PEEK pipe without adding a crystalline polyaryletherketone-based nucleating agent in the prior art;
[0037] Figure 2 This is a photo of the antistatic PEEK pipe obtained in Example 1;
[0038] Figure 3 Comparative photographs of the antistatic PEEK pipe obtained in the prior art without adding a crystalline poly(aryletherketone)-based nucleating agent PEEK and Example 1. DETAILED DESCRIPTION
[0039] The specific implementation methods of the present invention are further described in detail below in conjunction with the examples. The examples described are only specific descriptions of the claims of the present invention, and the claims include but are not limited to the contents of the examples described. Unless otherwise specified, the reagents and materials described in the following examples are all obtained from commercial channels; the experimental methods described are all conventional methods unless otherwise specified.
[0040] Embodiment 1:
[0041] (1) preparing a 0.5wt% ketimine-type polyetheretherketoneketone tetrahydrofuran solution, adding a 0.2wt% carbon nanotube under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding a 0.5wt% 100-mesh PEEK ultrafine powder, wherein the PEEK has a melt index of 80g / 10min; continuing ultrasonic dispersion for 30 minutes, adding a pH=1.0 hydrochloric acid aqueous solution dropwise under ultrasonic conditions, wherein the volume of the hydrochloric acid aqueous solution is 20% of the volume of tetrahydrofuran; treating under reflux for 10 hours, filtering, and washing with pH=1.0 acid, water, and ethanol three times each to obtain an antistatic masterbatch;
[0042] (2) 60 parts of PEEK powder (100 mesh) with a melt index of 5 g / 10 min, 10 parts of PEEK with a melt index of 100 g / 10 min and 30 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 10000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, the speed of the twin-screw extruder is 220 r / min; the temperature of the feeding section is 260° C.; the temperature of the compression section and the side feeding section is 370° C.; the temperature of the homogenization section is 380° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0043] (3) The antistatic polyetheretherketone pipe material obtained in step (2) is used to extrude a pipe with an outer diameter of 4 mm and a wall thickness of 1 mm. The antistatic polyetheretherketone pipe material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 40 r / min; the temperature of the feeding section is 300°C; the temperature of the compression section is 370°C; the temperature of the homogenization section is 380°C; the temperature of the die head is 370°C; and the pulling rate is 100 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.1 MPa, and the sizing process is carried out in three sections using three 6-meter-long high-temperature sizing boxes, wherein the first section cooling sizing temperature is 320°C, the second section crystallization sizing temperature is 280°C, and the third section annealing sizing temperature is 200°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, and the pulling rate is 600 mm / min. The tensile strength of the pipe is 99.6MPa, the bursting pressure is 11MPa, and the surface resistance is 1.5×10 7 Ω / sq.
[0044] Embodiment 2:
[0045] (1) preparing a 0.5wt% hemiketal polyetheretherketoneketone N,N-dimethylformamide solution; adding 1.0wt% acidified carbon nanotubes under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding 0.5wt% 300-mesh PEEK ultrafine powder, wherein the melt index of the PEEK is 144g / 10min; continuing ultrasonic dispersion for 30 minutes, adding a sulfuric acid aqueous solution with a pH value of 1.0 dropwise under ultrasonic conditions, wherein the volume of the sulfuric acid aqueous solution is 20% of the volume of N,N-dimethylformamide; treating under reflux for 10 hours and filtering, and washing with acid / water at pH value of 1.0 and washing with ethanol three times each to obtain an antistatic filler masterbatch;
[0046] (2) 94.8 parts of PEEK powder (500 mesh) with a melt index of 30 g / 10 min, 5 parts of PEEK with a melt index of 150 g / 10 min, and 0.2 parts of the antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 230 r / min; the temperature of the feeding section is 300° C.; the temperature of the compression section and the side feeding section is 380° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 365° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe material is obtained;
[0047] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 10 mm and a wall thickness of 2 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 280°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 350°C; and the pulling rate is 10 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 300°C, the crystallization sizing temperature of the second section is 260°C, and the annealing sizing temperature of the third section is 190°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 630 mm / min. The tensile strength of the pipe is 95.4MPa, the bursting pressure is 5MPa, and the surface resistance is 2.1×10 8 Ω / sq.
[0048] Embodiment 3:
[0049] (1) preparing a 5.0wt% ketimine-type biphenyl-type polyetheretherketone N,N-dimethylacetamide solution; adding 1.0wt% acidified carbon nanotubes under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding 5.0wt% 300-mesh PEEK ultrafine powder, wherein the melt index of the PEEK is 144g / 10min; continuing ultrasonic dispersion for 30 minutes, adding a pH=1.0 methanesulfonic acid aqueous solution dropwise under ultrasonic conditions, wherein the volume of the methanesulfonic acid aqueous solution is 20% of the volume of N,N-dimethylacetamide; treating under reflux for 10 hours, filtering, and washing with pH=1.0 acid, water, and ethanol three times each to obtain an antistatic filler masterbatch;
[0050] (2) 87 parts of PEEK powder (800 mesh) with a melt index of 30 g / 10 min, 5 parts of hyperbranched polyaryletherketone and 8 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a rate of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 280 r / min; the temperature of the feeding section is 260° C.; the temperature of the compression section and the side feeding section is 380° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0051] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 20 mm and a wall thickness of 3 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 310°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 500 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 310°C, the crystallization sizing temperature of the second section is 270°C, and the annealing sizing temperature of the third section is 180°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 700 mm / min. The tensile strength of the pipe is 96.0MPa, the bursting pressure is 6.5MPa, and the surface resistance is 0.8×10 9 Ω / sq.
[0052] Embodiment 4:
[0053] (1) preparing a 5.0 wt% hemiketal all-biphenyl polyetheretherketone dichloromethane solution; adding 1.0 wt% acidified carbon nanotubes under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 min, adding 5.0 wt% 300 mesh PEEK ultrafine powder, wherein the melt index of the PEEK is 144 g / 10 min; continuing ultrasonic dispersion for 30 min, adding a pH=1.0 benzenesulfonic acid aqueous solution dropwise under ultrasonic conditions, wherein the volume of the benzenesulfonic acid aqueous solution is 20% of the volume of dichloromethane; treating under reflux for 10 h, filtering, and washing with pH=1.0 acid, water, and ethanol three times each to obtain an antistatic filler masterbatch;
[0054] (2) 83 parts of PEEK powder (400 mesh) with a melt index of 30 g / 10 min, 5 parts of polyaryletherketone liquid crystal and 12 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 250 r / min; the temperature of the feeding section is 290° C.; the temperature of the compression section and the side feeding section is 380° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0055] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 50 mm and a wall thickness of 1 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 300°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 30 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.8 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 320°C, the crystallization sizing temperature of the second section is 280°C, and the annealing sizing temperature of the third section is 200°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 710 mm / min. The tensile strength of the pipe is 96.7MPa, the bursting pressure is 9.2MPa, and the surface resistance is 0.8×10 8 Ω / sq.
[0056] Embodiment 5:
[0057] (1) preparing a ketimine type all-biphenyl type polyetheretherketoneketone 1,2-dichloroethane solution with a mass fraction of 5.0wt%; adding a mass fraction of 1.0wt% of acidified carbon nanotubes under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding a mass fraction of 5.0wt% of 300 mesh PEEK ultrafine powder, wherein the melt index of the PEEK is 144g / 10min; continuing ultrasonic dispersion for 30 minutes, adding a trifluoroacetic acid aqueous solution with a pH of 1.0 dropwise under ultrasonic conditions, wherein the volume of the trifluoroacetic acid aqueous solution is 20% of the volume of 1,2-dichloroethane; treating under reflux for 10 hours, filtering, and washing with acid at pH = 1.0, washing with water, and washing with ethanol three times each to obtain an antistatic filler masterbatch;
[0058] (2) 89 parts of PEEK powder (1000 mesh) with a melt index of 30 g / 10 min, 5 parts of polyaryletherketone liquid crystal and 6 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 270 r / min; the temperature of the feeding section is 280°C; the temperature of the compression section and the side feeding section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the extrusion die is 385°C; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0059] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 50 mm and a wall thickness of 5 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 300°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 30 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 320°C, the crystallization sizing temperature of the second section is 250°C, and the annealing sizing temperature of the third section is 200°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 750 mm / min. The tensile strength of the pipe is 95.8MPa, the bursting pressure is 10.4MPa, and the surface resistance is 0.6×10 9 Ω / sq.
[0060] Embodiment 6:
[0061] (1) preparing a chloroform solution of hemiketal-type all-biphenyl-type polyetheretherketoneketone with a mass fraction of 5.0wt%; adding acidified carbon nanotubes with a mass fraction of 1.0wt% under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding 300-mesh PEEK ultrafine powder with a mass fraction of 5.0wt%, wherein the melt index of the PEEK is 144g / 10min; continuing ultrasonic dispersion for 30 minutes, dripping a trifluorobenzenesulfonic acid aqueous solution with a pH value of 1.0 under ultrasonic conditions, wherein the volume of the trifluorobenzenesulfonic acid aqueous solution is 20% of the volume of chloroform; treating under reflux for 10 hours, filtering, and washing with acid at pH value of 1.0, washing with water, and washing with ethanol three times each to obtain an antistatic filler masterbatch;
[0062] (2) 89.8 parts of PEEK powder (600 mesh) with a melt index of 30 g / 10 min, 5 parts of polyaryletherketone liquid crystal and 5.2 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for extrusion granulation, the speed of the twin-screw extruder is 280 r / min; the temperature of the feeding section is 270° C.; the temperature of the compression section and the side feeding section is 380° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe material is obtained;
[0063] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 18 mm and a wall thickness of 2 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 310°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 30 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 320°C, the crystallization sizing temperature of the second section is 280°C, and the annealing sizing temperature of the third section is 200°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 760 mm / min. The tensile strength of the pipe is 95.7MPa, the bursting pressure is 7.2MPa, and the surface resistance is 0.4×10 9 Ω / sq.
[0064] Embodiment 7:
[0065] (1) preparing a 5.0wt% ketimine-type all-biphenyl-type polyetheretherketone biphenyl ketone N-methylpyrrolidone solution; adding a 1.0wt% acidified carbon nanotube under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding a 5.0wt% 300-mesh PEEK ultrafine powder, wherein the PEEK has a melt index of 144g / 10min; continuing ultrasonic dispersion for 30 minutes, and dripping a pH=1.0 trifluorobenzenesulfonic acid aqueous solution under ultrasonic conditions, wherein the volume of the trifluorobenzenesulfonic acid aqueous solution is 20% of the volume of N-methylpyrrolidone; treating under reflux for 10 hours, filtering, and washing with pH=1.0 acid, water, and ethanol three times each to obtain an antistatic filler masterbatch;
[0066] (2) 94.8 parts of PEEK powder (700 mesh) with a melt index of 30 g / 10 min, 5 parts of polyaryletherketone liquid crystal, and 0.2 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 260 r / min; the temperature of the feeding section is 260° C.; the temperature of the compression section and the side feeding section is 270° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0067] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 18 mm and a wall thickness of 2 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 300°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 30 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 310°C, the crystallization sizing temperature of the second section is 280°C, and the annealing sizing temperature of the third section is 190°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 780 mm / min. The tensile strength of the pipe is 95MPa, the bursting pressure is 6.5MPa, and the surface resistance is 0.9×10 9 Ω / sq.
[0068] Embodiment 8:
[0069] (1) preparing a 5.0wt% hemiketal-type all-biphenyl-type polyetheretherketone biphenyl ketone N-methylpyrrolidone solution; adding 1.0wt% acidified carbon nanotubes under ultrasonic dispersion conditions; continuing ultrasonic dispersion for 30 minutes, adding 5.0wt% 300-mesh PEEK ultrafine powder, wherein the melt index of the PEEK is 144g / 10min; continuing ultrasonic dispersion for 30 minutes, dripping a pH=1.0 trifluorobenzenesulfonic acid aqueous solution under ultrasonic conditions, wherein the volume of the trifluorobenzenesulfonic acid aqueous solution is 20% of the volume of N-methylpyrrolidone; treating under reflux for 10 hours, filtering, and washing with acid at pH=1.0, washing with water, and washing with ethanol three times each to obtain an antistatic filler masterbatch;
[0070] (2) 80 parts of PEEK powder (1000 mesh) with a melt index of 30 g / 10 min, 5 parts of polyaryletherketone liquid crystal and 15 parts of antistatic filler masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a speed of 20,000 r / min for 10 min to obtain a mixed powder; the mixed powder is uniformly added to a twin-screw extruder for melt extrusion and granulation, and the speed of the twin-screw extruder is 260 r / min; the temperature of the feeding section is 270° C.; the temperature of the compression section and the side feeding section is 380° C.; the temperature of the homogenization section is 390° C.; the temperature of the extrusion die is 385° C.; after extrusion and granulation, a high-strength antistatic polyetheretherketone (PEEK) pipe raw material is obtained;
[0071] (3) The antistatic polyetheretherketone pipe raw material obtained in step (2) is used to extrude a pipe with an outer diameter of 18 mm and a wall thickness of 2 mm. The antistatic polyetheretherketone pipe raw material is added to a single screw extruder through a feeder for melting, wherein the speed of the single screw extruder is 60 r / min; the temperature of the feeding section is 290°C; the temperature of the compression section is 380°C; the temperature of the homogenization section is 390°C; the temperature of the die head is 370°C; and the pulling rate is 30 mm / min. After extrusion through the die head, vacuum sizing is performed, wherein the vacuum degree is 0.5 MPa. The sizing process is carried out in three sections using three 10-meter-long high-temperature sizing boxes, wherein the cooling sizing temperature of the first section is 320°C, the crystallization sizing temperature of the second section is 280°C, and the annealing sizing temperature of the third section is 200°C; the sizing pipe is cooled, pulled, cut and curled to obtain an antistatic PEEK pipe, wherein the pulling rate is 900 mm / min. The tensile strength of the pipe is 98.4MPa, the bursting pressure is 5.6MPa, and the surface resistance is 0.8×10 9 Ω / sq.
[0072] In summary: From the above embodiments, it can be seen that the components, proportions and processes of each embodiment are different, among which the tensile strength, bursting pressure and surface resistance of the material obtained in Example 1 achieve the most optimized effect. It can be concluded that the present invention achieves the best performance of the material through the synergistic effect of raw materials, proportions and reaction processes.
Claims
1. A high-strength antistatic polyetheretherketone (PEEK) pipe, characterized in that: Its preparation method comprises the following steps: (1) dissolving a soluble precursor of a crystalline polyaryletherketone-based nucleating agent in an organic solvent to obtain a precursor solution with a mass fraction of 0.5-5.0wt%; then adding an antistatic filler under ultrasonic dispersion conditions, wherein the mass fraction of the antistatic filler in the precursor solution is 0.1-2.0wt%, and after ultrasonic dispersion for 10-60min, adding 100-300 mesh PEEK ultrafine powder with a mass fraction of 0.5-5.0wt%; and after ultrasonic dispersion for 10-60min, adding a protonic acid aqueous solution with a pH of 1-5, wherein the protonic acid aqueous solution The volume ratio of the solution to the organic solvent is 20-60%:1; after refluxing for 5-15 hours, the mixture is filtered, and then washed with an acid having a pH value of 1-5, washed with water, and washed with ethanol to obtain an antistatic masterbatch; the antistatic filler is evenly distributed in a single layer on the surface of the PEEK ultrafine powder; the crystalline polyaryletherketone-based nucleating agent is evenly attached to the surface of the PEEK ultrafine powder; the crystalline polyaryletherketone-based nucleating agent bonds the antistatic filler to the surface of the PEEK ultrafine powder; the antistatic filler is a carbon nanotube, and the melt index of the PEEK ultrafine powder is 80-144g / 10min; (2) According to the mass ratio of 94.8-60:5-20:0.2-30, PEEK powder with a melt index of 5-50g / 10min and a mesh size of 100-1000, a polyaryletherketone-based plasticizer and the antistatic masterbatch obtained in step (1) are uniformly mixed in a high-speed stirring mixer at a rate of 10000-20000r / min for 10-30min, and then extruded and granulated to obtain a high-strength antistatic polyetheretherketone pipe raw material; among the raw materials: except for the antistatic filler, the remaining components are polyaryletherketone, the antistatic filler content is 0.1-10 parts, the crystalline polyaryletherketone-based nucleating agent content is 0.1-10 parts, the polyaryletherketone-based plasticizer content is 5-20 parts, and the PEEK content is 60-94.8 parts; (3) the antistatic polyetheretherketone pipe raw material obtained in step (2) is melted, extruded, vacuum sized, cooled, pulled, cut or curled to obtain a high-strength antistatic polyetheretherketone pipe; the vacuum sizing is as follows: the vacuum degree is 0.1-0.8MPa, three 6-10 m high temperature sizing boxes are used for heating in three stages, the first stage cooling sizing temperature is 300-320°C, the second stage crystallization sizing temperature is 250-280°C, and the third stage annealing sizing temperature is 180-200°C; the pulling rate is 500-1000mm / min; The soluble precursor of the crystalline polyaryletherketone-based nucleating agent used in step (1) is ketimine-type polyetheretherketoneketone, hemiketal-type polyetheretherketoneketone, ketimine-type all-biphenyl-type polyetheretherketone, hemiketal-type all-biphenyl-type polyetheretherketone, ketimine-type all-biphenyl-type polyetheretherketoneketone, hemiketal-type all-biphenyl-type polyetheretherketoneketone, ketimine-type all-biphenyl-type polyetheretherketonebiphenylketone or hemiketal-type all-biphenyl-type polyetheretherketonebiphenylketone, and their structures are shown in the following structural formulas 1-8 in order; Structural formula 1 Ketimine type polyetheretherketoneketone 10≤n≤50000 Structural formula 2 Hemiketal type polyetheretherketoneketone 10≤n≤50000 Structural formula 3-ketimine type all-biphenyl type polyetheretherketone 10≤n≤50000 Structural formula 4 Hemiketal type all-biphenyl type polyetheretherketone 10≤n≤50000 Structural formula 5-ketoimine type all-biphenyl type polyetheretherketoneketone 10≤n≤50000 Structural formula 6 Hemiketal type all-biphenyl type polyetheretherketoneketone 10≤n≤50000 Structural formula 7 Ketimine type all-biphenyl type polyetheretherketone biphenyl ketone 10≤n≤50000 Structural formula 8 Hemiketal type all-biphenyl type polyetheretherketone biphenyl ketone 10≤n≤50000; The polyaryletherketone-based plasticizer used in step (2) is PEEK or hyperbranched polyaryletherketone or polyaryletherketone liquid crystal having a melt index of 100-150 g / 10 min, and the structure of the hyperbranched polyaryletherketone and polyaryletherketone liquid crystal is shown in the following structural formula 9-10; Hyperbranched polyaryletherketone of structural formula 9, wherein x, x1, x2, y, y1, y2, z, z1, z2 are all integers greater than 3 and less than 100; Structural formula 10: polyaryletherketone liquid crystal, wherein n is an integer of 10≤n≤50000, the total amount of two repeating units is n, and x represents the proportion of the repeating unit to n, wherein 0.1≤x≤0.
9.
2. A high-strength antistatic polyetheretherketone (PEEK) pipe according to claim 1, characterized in that: The organic solvent used in step (1) is tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, 1,2-dichloroethane, chloroform or N-methylpyrrolidone.
3. The high-strength antistatic polyetheretherketone (PEEK) pipe according to claim 1, characterized in that: The protonic acid used in step (1) is hydrochloric acid, sulfuric acid, methanesulfonic acid, benzenesulfonic acid, trifluoroacetic acid or trifluorobenzenesulfonic acid.
4. The high-strength antistatic polyetheretherketone (PEEK) pipe according to claim 1, characterized in that: The carbon nanotubes described in step (1) are acidified carbon nanotubes.
5. The high-strength antistatic polyetheretherketone (PEEK) pipe according to claim 1, characterized in that: The extrusion in step (2) is as follows: a twin-screw extruder is used, wherein the rotation speed is 220-280r / min; the temperature of the feeding section is 250-300°C; the temperature of the compression section and the side feeding section is 370-380°C; the temperature of the homogenization section is 380-390°C; and the temperature of the extrusion die is 365-385°C.
6. The high-strength antistatic polyetheretherketone (PEEK) pipe according to claim 1, characterized in that: The extrusion in step (3) is as follows: a single screw extruder is used, wherein the rotation speed is 40-60r / min; the temperature of the feeding section is 280-320°C; the temperature of the compression section is 370-380°C; the temperature of the homogenization section is 380-390°C; the temperature of the die head is 350-370°C; and the pulling rate is 10-500mm / min.
Citation Information
Patent Citations
Method for preparing nano-silver wire
CN109848432A
High-toughness polyetheretherketone-based antistatic composite material and preparation method thereof
CN112940450A